2005
DOI: 10.1109/tmag.2005.854973
|View full text |Cite
|
Sign up to set email alerts
|

Flux-linkage calculation in permanent-magnet motors using the frozen permeabilities method

Abstract: Finite-element analysis can be used to determine the magnetization characteristics in terms of curves of flux-linkage against current or rotor position. The "frozen permeabilities" technique is presented as a method of apportioning flux-linkage contributions to the phase currents and permanent magnets, and for inductance calculations. Results from a split-phase interior permanent magnet motor are presented and compared with experimental data. Drawbacks to the method are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(41 citation statements)
references
References 2 publications
0
41
0
Order By: Relevance
“…The induced mutual flux linkages in all phases can be determined by running frozen permeability finite element simulations for each phase in turn. 4,5 The mutual, self-, and total flux linkages for phases 1 and 4 ͑determined from a combination of nonlinear and frozen permeability solutions͒, for windings polarities of N-S-N-S are given in Figs. 4 and 5, respectively.…”
Section: Finite Element Modeling Of Mutual Couplingmentioning
confidence: 99%
“…The induced mutual flux linkages in all phases can be determined by running frozen permeability finite element simulations for each phase in turn. 4,5 The mutual, self-, and total flux linkages for phases 1 and 4 ͑determined from a combination of nonlinear and frozen permeability solutions͒, for windings polarities of N-S-N-S are given in Figs. 4 and 5, respectively.…”
Section: Finite Element Modeling Of Mutual Couplingmentioning
confidence: 99%
“…Figure 5a shows the total magnetic flux distributions of proposed model under no-load condition. In addition, the frozen permeability method (FPM) [18] is used to obtain the separated magnetic flux produced by the rotor field windings (FWs) or produced by the assisted-PM, as indicated in Figure 5b,c. It is observed that the magnetic flux direction of the PM in the rotor core is opposite to that produced by the FWs.…”
Section: Principlementioning
confidence: 99%
“…This is achieved using the frozen permeability method as described in the following. Such a technique has been used in the past for different purposes: to model the electrical machine under saturated conditions [22], to weigh the flux linkage contributions to the average torque [23], and to segregate the torque components [24]. In all these works, only magnetostatic analysis has been adopted for their purpose, since the high frequency analysis was not considered.…”
Section: Finite Element Simulationsmentioning
confidence: 99%